Parliamentary oversight of emergency measures and policies – A safeguard of democracy during a crisis? - Värttö, Mikko (Wiley, 2025)
The article discusses the role of parliamentary oversight of emergency measures and policies in increasing democratic resilience and recovery from the COVID-19 pandemic. The study on the Finnish Parliament is conducted by analyzing the statements of the Constitutional Law Committee, whose role is to conduct a parliamentary constitutional review of governmental bills. The main focus of the analysis is on the Committee's reviews of the constitutionality of the emergency measures and the procedures of law drafting. The research indicates that the committee considered the restrictions and exceptions of fundamental rights as proportional and necessary to prevent the overburdening of the healthcare system in most cases. However, the justifications for the emergency measures were often lacking, and the parliament's right to receive information was compromised. These deficits undermined the Parliament's capacity to oversee emergency measures and policies. The parliamentary constitutional review during the pandemic could still serve a critical complementary function by protecting fundamental rights and democratic values.